Development and Performance of an Algorithm to Estimate the Child-Turcotte-Pugh Score From a National Electronic Healthcare Database - Kaplan, David E.; Dai, Feng; Aytaman, Ayse; Baytarian, Michelle; Fox, Rena; Hunt, Kristel; Knott, Astrid; Pedrosa, Marcos; Pocha, Christine; Mehta, Rajni; Duggal, Mona; Skanderson, Melissa; et al. (Clinical gastroenterology and hepatology, 2015)
The Child-Turcotte-Pugh (CTP) score is a widely used and validated predictor of long-term survival in cirrhosis. The CTP score is a composite of 5 subscores, 3 based on objective clinical laboratory values and 2 subjective variables quantifying the severity of ascites and hepatic encephalopathy. To date, no system to quantify CTP score from administrative databases has been validated. The Veterans Outcomes and Costs Associated with Liver Disease study is a multicenter collaborative study to evaluate the outcomes and costs of hepatocellular carcinoma in the U.S. Veterans Health Administration. We developed and validated an algorithm to calculate electronic CTP (eCTP) scores by using data from the Veterans Health Administration Corporate Data Warehouse. Multiple algorithms for determining each CTP subscore from International Classification of Diseases version 9, Common Procedural Terminology, pharmacy, and laboratory data were devised and tested in 2 patient cohorts. For each cohort, 6 site investigators (Boston, Bronx, Brooklyn, Philadelphia, Minneapolis, and West Haven VA Medical Centers) were provided cases from which to determine validity of diagnosis, laboratory data, and clinical assessment of ascites and encephalopathy. The optimal algorithm (designated eCTP) was then applied to 30,840 cirrhotic patients alive in the first quarter of 2008 for whom 5-year overall and transplant-free survival data were available. The ability of the eCTP score and other disease severity scores (Charlson-Deyo index, Veterans Aging Cohort Study index, Model for End-Stage Liver Disease score, and Cirrhosis Comorbidity) to predict survival was then assessed by Cox proportional hazards regression. Spearman correlations for administrative and investigator validated laboratory data in the HCC and cirrhotic cohorts, respectively, were 0.85 and 0.92 for bilirubin, 0.92 and 0.87 for albumin, and 0.84 and 0.86 for international normalized ratio. In the HCC cohort, the overall eCTP score matched 96% of patients to within 1 point of the chart-validated CTP score (Spearman correlation, 0.81). In the cirrhosis cohort, 98% were matched to within 1 point of their actual CTP score (Spearman, 0.85). When applied to a cohort of 30,840 patients with cirrhosis, each unit change in eCTP was associated with 39% increase in the relative risk of death or transplantation. The Harrell C statistic for the eCTP (0.678) was numerically higher than those for other disease severity indices for predicting 5-year transplant-free survival. Adding other predictive models to the eCTP resulted in minimal differences in its predictive performance. We developed and validated an algorithm to extrapolate an eCTP score from data in a large administrative database with excellent correlation to actual CTP score on chart review. When applied to an administrative database, this algorithm is a highly useful predictor of survival when compared with multiple other published liver disease severity indices.